Extraction Protocol for Parallel Analysis of Proteins and DNA from Ancient Teeth and Dental Calculus - Chocholova, Eva; Roudnicky, Pavel; Potesil, David; Fialova, Dana; Krystofova, Karolina; Drozdova, Eva; Zdrahal, Zbynek (Journal of proteome research, 2023)
Dental calculus is becoming a crucial material in the study of past populations with increasing interest in its proteomic and genomic content. Here, we suggest further development of a protocol for analysis of ancient proteins and a combined approach for subsequent ancient DNA extraction. We tested the protocol on recent teeth, and the optimized protocol was applied to ancient tooth to limit the destruction of calculus as it is a precious and irreplaceable source of dietary, microbiological, and ecological information in the archeological context. Finally, the applicability of the protocol was demonstrated on samples of the ancient calculus.
Keywords: dental calculus; bioarcheology; paleoproteomics; ancient DNA; ancient proteins